Distribution and favorable prognostic implication of genomic EGFR alterations in IDH‐wildtype glioblastoma. (13th June 2022) - Higa, Nayuta; Akahane, Toshiaki; Hamada, Taiji; Yonezawa, Hajime; Uchida, Hiroyuki; Makino, Ryutaro; Watanabe, Shoji; Takajo, Tomoko; Yokoyama, Seiya; Kirishima, Mari; Matsuo, Kei; Fujio, Shingo; et al.
Abstract: Background: We aimed to evaluate the mutation profile, transcriptional variants, and prognostic impact of the epidermal growth factor receptor ( EGFR ) gene in isocitrate dehydrogenase ( IDH )‐wildtype glioblastomas (GBMs). Methods: We sequenced EGFR, evaluated the EGFR splicing profile using a next‐generation sequencing oncopanel, and analyzed the outcomes in 138 grade IV IDH ‐wildtype GBM cases. Results: EGFR mutations were observed in 10% of GBMs. A total of 23.9% of the GBMs showed EGFR amplification. Moreover, 25% of the EGFR mutations occurred in the kinase domain. Notably, EGFR alterations were a predictor of good prognosis ( p = 0.035). GBM with EGFR alterations was associated with higher Karnofsky Performance Scale scores ( p = 0.014) and lower Ki‐67 scores ( p = 0.005) than GBM without EGFR alterations. EGFRvIII positivity was detected in 21% of EGFR ‐amplified GBMs. We identified two other EGFR variants in GBM cases with deletions of exons 6–7 (Δe 6–7) and exons 2–14 (Δe 2–14). In one case, the initial EGFRvIII mutation transformed into an EGFR Δe 2–14 mutation during recurrence. Conclusions: We found that the EGFR gene profiles of GBM differ among cohorts and that EGFR alterations are good prognostic markers of overall survival in patients with IDH ‐wildtype GBM. Additionally, we identified rare EGFR variants with longitudinal and temporal transformations of EGFRvIII . Abstract : The frequency of epidermal growth factor receptor ( EGFR ) mutations was low but the frequency of EGFR mutations in the kinase domain was high in isocitrate dehydrogenase‐wildtype glioblastomas (GBMs) in our cohort. Notably, in this study, GBM with EGFR alterations had a better outcome than GBM without them.